Gray matter, white matter and cerebrospinal fluid abnormalities in Parkinson’s disease: A voxel-based morphometry study - Nyatega, Charles Okanda; Qiang, Li; Adamu, Mohammed Jajere; Kawuwa, Halima Bello (Frontiers in Psychiatry, 2022)
Parkinson's disease (PD) is a chronic neurodegenerative disorder characterized by bradykinesia, tremor, and rigidity among other symptoms. With a 70 percent cumulative prevalence of dementia in PD, cognitive impairment and neuropsychiatric symptoms are frequent. In this study, we looked at anatomical brain differences between groups of PD patients and controls. 138 people with Parkinson's disease were compared to 64 age-matched healthy people using voxel-based morphometry (VBM). VBM is a fully automated technique that allows for the identification of regional differences in gray matter (GM), white matter (WM) and Cerebrospinal fluid (CSF) allowing for an objective comparison of brains of different groups of people. We used statistical parametric mapping (SPM12) for image processing and statistical analysis. In comparison to controls, PD patients had lower GM volumes in the left middle cingulate, left lingual gyrus, right calcarine and left fusiform gyrus, also PD patients indicated lower WM volumes in the right middle cingulate, left lingual gyrus, right calcarine and left inferior occipital gyrus. Moreover, PD patient group demonstrated higher CSF in the left caudate compared to the controls. Our findings shed light on the role of the brain in PD and may aid in a better understanding of the events that occur in PD patients.